The association between obesity, hypertension and left ventricular mass in adolescents - ŞAYLAN ÇEVİK, BERNA (WALTER DE GRUYTER GMBH, 2017)
Background: Obesity and hypertension (HT) are well known cardiac risk factors. Our goal was to show that even if arterial blood pressure (BP) measurements of obese adolescents are normal during clinical examination, ambulatory blood pressure monitoring (ABPM) can be high, may include cardiac involvement and can also detect left ventricular mass indices (LVMI) value for obese adolescents to diagnose left ventricular hypertrophy (LVH). Methods: This study included 130 children (57 obese hypertensive, 36 obese normotensive, 14 normal weight hypertensive and 23 normal weight normotensive). Adolescents whose BP was measured during clinical examination, after 24-h BP was detected using ABPM, were examined with echocardiography for calculation of LVMI to determine cardiac risk factors for LVH. Results: There was a significant difference between the LVMI of obese-normotensive and obese-hypertensive adolescents, which showed the effect of obesity on LVMI independent of HT. Twenty (35.7%) of 56 obese adolescents with HT detected with ABPM had normal BP measurements during clinical examination. Dipper and nondipper features of obese adolescents were significantly higher in ABPM than those with normal body mass index. When the cutoff LVMI value for LVH was set at >= 38 g/m(2.7), 38.9% of obese-normotensive and 50.9% of obese-hypertensive subjects had LVH; however, when the cutoff value was set at >= 51 g/m(2.7), the rates were 2.8% and 19.3%, respectively. Conclusions: Obesity is a risk factor for LVH independent of HT. To identify masked HT, 24-h ABPM and cardiac examination should be routinely performed in obese adolescents. Using a limit of LVMI >= 38 g/m(2.7) in evaluating LVH secondary to HT in obese individuals may lead to an overestimated diagnosis rate of LVH.
Keywords: adolescence; hypertension; left ventricular hypertrophy; left ventricular mass index; obesity; AMBULATORY BLOOD-PRESSURE; CHILDREN; HYPERTROPHY; INDEX